The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1349-7006.2011.01963.x
|View full text |Cite
|
Sign up to set email alerts
|

GM3 suppresses anchorage‐independent growth via Rho GDP dissociation inhibitor beta in melanoma B16 cells

Abstract: Ly-GDI, Rho GTPase dissociation inhibitor beta, was found to be expressed parallel to the GM3 level in mouse B16 cells whose GM3 contents were modified by B4galt6 sense, B4galt6 antisense cDNA, or St3galt5 siRNA transfection. Ly-GDI expression was increased on GM3 addition to these cells and decreased with D-PDMP treatment, a glucosylceramide synthesis inhibitor. Suppression of GM3 or Ly-GDI by RNAi was concomitantly associated with an increase in anchorage-independent growth in soft agar. These results clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…RhoGDI2 also promotes tumor growth, invasion and metastasis in ovarian carcinoma (Stevens et al, 2011) and in breast cancer (Gu et al, 2008;Zhang et al, 2009;Zhang and Zhang, 2006). It has been reported that RhoGDI2 suppresses anchorage-independent growth in melanoma B16 cells (Wang et al, 2011). In our study, we demonstrated that depletion of Myo7a inhibited melanoma cell motility by downregulating expression of RhoGDI2.…”
Section: Discussionsupporting
confidence: 63%
“…RhoGDI2 also promotes tumor growth, invasion and metastasis in ovarian carcinoma (Stevens et al, 2011) and in breast cancer (Gu et al, 2008;Zhang et al, 2009;Zhang and Zhang, 2006). It has been reported that RhoGDI2 suppresses anchorage-independent growth in melanoma B16 cells (Wang et al, 2011). In our study, we demonstrated that depletion of Myo7a inhibited melanoma cell motility by downregulating expression of RhoGDI2.…”
Section: Discussionsupporting
confidence: 63%
“…These results give further support to the notion that GM3 reduction enhances invasive proliferating ability of B16 cells in rigorous condition. It is also the characteristic of tumor cells that the proliferation was deregulated and the cells can escape the rigorous environment (Wang et al, 2011).…”
Section: Gm3 Suppresses B16 Invasive Proliferationmentioning
confidence: 99%
“…To keep the discussion focused, we will discuss the relationship between GM3 contents and their abilities to regulate proto-oncogenes or tumor suppressor genes, which in turn mediate melanoma metastasis. To screen GM3 target genes, we obtained cells (CSSH-1) that overexpressed B4galt6 cDNA and cells (CAH-3) that suppressed its expression, which in turn result in GM3 modulation [4], [5]. In the CSSH-1 cells, GM3 contents were doubled, but in the CAH-3 cells, GM3 expression was halved compared with vector transfectant control, SM-1 and CM-1, respectively [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…To screen GM3 target genes, we obtained cells (CSSH-1) that overexpressed B4galt6 cDNA and cells (CAH-3) that suppressed its expression, which in turn result in GM3 modulation [4], [5]. In the CSSH-1 cells, GM3 contents were doubled, but in the CAH-3 cells, GM3 expression was halved compared with vector transfectant control, SM-1 and CM-1, respectively [4], [5]. To further confirm the roles of GM3 in melanoma cells, St3gal5 silenced cells were established by transfecting B16 cells with St3gal5 siRNA and it was found that the introduction of St3gal5 siRNA to B16 cells resulted in GM3 depletion as compared with the scrambled siRNA transfectant control [4], [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation